Assembly, annotation, and comparative analysis of Ipomoea chloroplast genomes provide insights into the parasitic characteristics of Cuscuta species - Wang, Yu; Xu, Jing; Hu, Bin; Dong, Chunxing; Sun, Jin; Li, Zixian; Ye, Kangzhuo; Deng, Fang; Wang, Lulu; Aslam, Mohammad; Lv, Wenliang; Qin, Yuan; et al. (Frontiers in Plant Science, 2023)
In the Convolvulaceae family, around 1650 species belonging to 60 genera are widely distributed globally, mainly in the tropical and subtropical regions of America and Asia. Although a series of chloroplast (cp) genomes in Convolvulaceae were reported and investigated, the evolutionary and genetic relationships among the chloroplast genomes of the Convolvulaceae family have not been extensively elucidated till now. This study first reported the complete chloroplast genome sequence of Ipomoea pes-caprae, a widely distributed coastal plant with medical values. The chloroplast genome of I. pes-caprae is 161667 bp in length, and the GC content is 37.56 %. The chloroplastic DNA molecule of I. pes-caprae is a circular structure composed of LSC (large-single-copy), SSC (small-single-copy), and IR (inverted repeat) regions, with the size of the three regions being 88210 bp, 12117 bp, and 30670 bp, respectively. The chloroplast genome of I. pes-caprae contains 141 genes, and 35 SSRs are identified in the chloroplast genome. Our research results provide important genomic information for the molecular phylogeny of I. pes-caprae. The Phylogenetic analysis of 28 Convolvulaceae chloroplast genomes showed that the relationship of I. pes-caprae with I. involucrata or I. obscura was much closer than that with other Convolvulaccae species. Further comparative analyses between the Ipomoea species and Cuscuta species revealed the mechanism underlying the formation of parasitic characteristics of Cuscuta species from the perspective of the chloroplast genome.